2014
DOI: 10.1371/journal.pone.0103023
|View full text |Cite
|
Sign up to set email alerts
|

How Much Is the Whole Really More than the Sum of Its Parts? 1 ⊞ 1 = 2.5: Superlinear Productivity in Collective Group Actions

Abstract: In a variety of open source software projects, we document a superlinear growth of production intensity () as a function of the number of active developers , with a median value of the exponent , with large dispersions of from slightly less than up to . For a typical project in this class, doubling of the group size multiplies typically the output by a factor , explaining the title. This superlinear law is found to hold for group sizes ranging from 5 to a few hundred developers. We propose two classes of mec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 70 publications
3
51
0
Order By: Relevance
“…34,35 The optimization of resources also implies that cities are expected to concentrate highquality specialized health care centers and professionals. For various diseases, however, generalist clinics and physicians are sufficient to provide appropriate primary care.…”
Section: Resultsmentioning
confidence: 99%
“…34,35 The optimization of resources also implies that cities are expected to concentrate highquality specialized health care centers and professionals. For various diseases, however, generalist clinics and physicians are sufficient to provide appropriate primary care.…”
Section: Resultsmentioning
confidence: 99%
“…The social loafing could, in fact, be observed when groups worked at diverse tasks, e.g. maze performance [19], evaluating a poem [20], song writing [21], brainstorming [22], reacting to proposals [23], judgmental tasks [24], research [25], software developing [26][27][28], pumping air [29], clapping [30], rowing [31], pulling a rope [32], swimming in relay races [33], job selection decisions, typing, and creativity problems [16,34].…”
Section: The Ringelmann Effect: Sociology Meets Physicsmentioning
confidence: 99%
“…Or she can be "the one" who is first exposed to a novel information, or who just shifts her psychology as a result of numerous conscious or unspecified unconscious reasons. In [37,38], it was shown that, close to a regime of criticality, the activities or productivity of a group of size s has a super-linear dependence on the group size. As mentioned, this may result from the appearance of a cooperative process and order involving a collective mode of traders defined by the build up of correlation between their contributions.…”
Section: Model Formulationmentioning
confidence: 99%
“…For smaller groups involved in creative activities, Ref. [38] documents exponents a ranging from 1 to more than 3, with a median value ≈ 4 3, thus typically much larger than in [39][40][41]. Ref.…”
Section: Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation